Report on the “National Planning workshop for Phase I of the Climate and Clean Air Coalition’s Paddy Rice Component in Bangladesh” - Sander, Björn Ole (2015)
The National Planning workshop for phase I of the Climate and Clean Air Coalition’s Paddy Rice Component was held in the Dhaka Bangladesh with the objectives to share experience on applying and scaling up the AWD technology for paddy rice in Bangladesh. Identify key areas, partners and aspects of work that need to be addressed. And to develop a detailed national plan for phase I of the CCAC Rice Component.